Employment dynamics and openness to trade in Finnish manufacturing - Satu Nurmi (The Research Institute of the Finnish Economy (ETLA), 2004)
This paper examines internationalisation and employment dynamics in the Finnish manufacturing sector 1980–2001 using plant and industry-level data. According to the results, there is a large heterogeneity in the patterns of international trade and employment across industries and over time. In addition, the effect of macroeconomic fluctuations on employment dynamics is considerable. The results suggest that higher international openness stimulates labour demand during periods of recovery. Higher import competition in the industry has negative employment consequences, whereas higher export intensity increases net employment growth. However, plant efficiency is an important factor in adjusting to the effects of import competition. Unexpectedly, there is also some evidence that trade liberalisation reduces job turnover especially in import-intensive sectors. – – Tässä tutkimuksessa analysoidaan kansainvälistymistä ja työllisyyskehitystä Suomen tehdasteollisuudessa ajanjaksolla 1980–2001 käyttäen toimipaikka- ja toimialatason aineistoja. Tulosten mukaan kaupan ja työllisyyden kehitys toimialojen välillä ja yli ajan on hyvin heterogeenista. Lisäksi suhdannevaihteluiden merkitys työllisyysdynamiikkaan on huomattava. Tulokset viittaavat siihen, että suurempi kansainvälinen avoimuus stimuloi työvoiman kysyntää lamasta elpymisen aikana. Suurempi tuontikilpailun aste toimialalla vaikuttaa työllisyyteen negatiivisesti, kun taas korkeampi vientiaste lisää nettotyöllisyyskasvua. Toimipaikan tehokkuus on kuitenkin tärkeä tekijä tuontikilpailun vaikutuksiin sopeutumisessa. Yllättäen, kaupan vapauttaminen näyttäisi vähentävän työpaikkojen vaihtuvuutta erityisesti tuonti-intensiivisillä toimialoilla.
Keywords: F16; J21; J23; L60; 330; Job flows; worker flows; internationalisation; manufacturing; Työpaikkavirrat; työntekijävirrat; kansainvälistyminen; teollisuus; Verarbeitendes Gewerbe; Globalisierung; Außenhandelsliberalisierung; Arbeitsnachfrage; Schätzung; Finnland